Scase, Wendy. 2022. Visible English: Graphic Culture, Scribal Practice, and Identity, c. 700–c. 1500. Turnhout: Brepols. Pp. xvii + 408. ISBN 9782503589420. - Carrillo-Linares, María José (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Book review of Scase, Wendy. 2022. Visible English: Graphic Culture, Scribal Practice, and Identity, c. 700–c. 1500. Turnhout: Brepols. Pp. xvii + 408. ISBN 9782503589420.